Impurity and correlation effects on transport in one-dimensional quantum wires - Enss, Tilman (Physical review. B, Condensed matter and materials physics, 2005)
We study transport through a one-dimensional quantum wire of correlated fermions connected to semi-infinite leads. The wire contains either a single impurity or two barriers, the latter allowing for resonant tunneling. In the leads the fermions are assumed to be noninteracting. The wire is described by a microscopic lattice model. Using the functional renormalization group we calculate the linear conductance for wires of mesoscopic length and for all relevant temperature scales. For a single impurity, either strong or weak, we find power-law behavior as a function of temperature. In addition, we can describe the complete crossover from the weak- to the strong-impurity limit. For two barriers, depending on the parameters of the enclosed quantum dot, we find temperature regimes in which the conductance follows power laws with “universal” exponents as well as nonuniversal behavior. Our approach leads to a comprehensive picture of resonant tunneling. We compare our results with those of alternative approaches.